Sports and The Global South Work, Play and Resistance In Sri Lanka - Biyanwila, S. Janaka (Global Culture and Sport Series, 2018)
This book reimagines the pleasures of sports and provides a critical perspective from the Global South. Analysing the spread of sports markets in Sri Lanka along with a range of struggles, the book highlights how the celebration of 'sportive nationalism,' promoting sports markets in the Global South reinforces patriarchal ethno-nationalist authoritarian sports cultures. By explaining how the realm of social reproduction involving households and communities is integral for play and sports, the book challenges the market-driven 'sports and development' agenda while arguing for a 'sports commons.' By foregrounding issues of justice and care, the book highlights how struggles for recognition, redistribution and representation are central to reimagining sports within an alternative notion of work, play and resistance.